Subsidized health regime: evolution and problems (1999)
The problems and distortions which have been generated during the process of establishing a subsidized health regime are examined in regard to fundamental aspects, focalization and distribution of subsidies, affiliation, insurance, contract making, financial aspects, surveillance and control, and decentralization. Some consequences could be the persistence of characteristics of the previous system and insufficient coverage.